2002
DOI: 10.1002/mrm.10082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bleomycin lung injury by nuclear magnetic resonance: Correlation between NMR relaxation times and lung water and collagen content

Abstract: The response of the NMR relaxation times (T 1 , CPMG T 2 , and Hahn T 2 ) to bleomycin-induced lung injury was studied in excised, unperfused rat lungs. NMR, histologic, and biochemical (collagen content measurement) analyses were performed 1, 2, 4, and 8 weeks after intratracheal instillation of saline (control lungs) or 10 U/kg bleomycin sulfate. The control lungs showed no important NMR, water content, histologic, or collagen content changes. The spin-spin relaxation times for the fast and intermediate comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 20 publications
4
25
0
Order By: Relevance
“…The three T 2 values became significantly prolonged in deflated lungs (27). Overall, their results were consistent with in vivo (28) and in vitro (29) T 2 studies of rat lungs using Hahn spin echo and multi-echo CPMG sequences. Furthermore, using cardiac-triggered SSFSE/HASTE sequences, Hatabu et al reported relatively long T 2 values of 60 to 100 ms in vivo in humans (17).…”
Section: Relaxation Properties Of Lung Tissue From Imaging Studiessupporting
confidence: 82%
See 2 more Smart Citations
“…The three T 2 values became significantly prolonged in deflated lungs (27). Overall, their results were consistent with in vivo (28) and in vitro (29) T 2 studies of rat lungs using Hahn spin echo and multi-echo CPMG sequences. Furthermore, using cardiac-triggered SSFSE/HASTE sequences, Hatabu et al reported relatively long T 2 values of 60 to 100 ms in vivo in humans (17).…”
Section: Relaxation Properties Of Lung Tissue From Imaging Studiessupporting
confidence: 82%
“…In particular, the fact that longer T 2 values are found when multiple spin echo sequences are used is consistent with bodily spin motion, e.g. perfusion and/or diffusion, within the background microscopic field gradients created by the multiple air/tissue interfaces within lung parenchyma, as discussed in the original articles (3,26-29). This same mechanism is most probably responsible for later observations by Ohno et al of an inter echo spacing dependence of lung signal from SSFSE/HASTE sequences (30).…”
Section: Relaxation Properties Of Lung Tissue From Imaging Studiesmentioning
confidence: 67%
See 1 more Smart Citation
“…It has been reported that lung fibrosis in BLM-treated mice is manifested by an increased T 2 , whereas lung inflammation is associated with decreased T 2 , suggesting that spinspin relaxation time may differentiate inflammation and fibrosis in the lung (27). However, an apparently opposite result has been observed in BLM-treated rats (28). To date, most of the studies suggest that signal intensity (S 0 ) measurements help differentiate lung inflammation and fibrosis (25,26,29,30).…”
Section: Distinguishing Lung Fibrosis From Inflammation By Mrimentioning
confidence: 99%
“…The feasibility of measuring lung water content and distribution by MRI techniques has been well recognized since the 1980s [2225]. However, so far quantitative techniques such as T2 relaxation and PD for inflammatory activity assessment in chronic interstitial lung disease have only been performed on animal models of bleomycin induced fibrosis [2628]. We aim to investigate for the first time the clinical utility of these methods applied to a cohort of patients with NSIP using a clinical 1.5T MRI scanner.…”
Section: Introductionmentioning
confidence: 99%